Are Children Born By Sectio Caesarea (SC) Correlated With Respiratory And Autoimmune Diseases? - Ita Yuliani; Jeltje Sophia Sondakh; Rita Yulifah (Poltekkes Kemenkes Surakarta, 2022)
Background: The incidence of pulmonary and autoimmune diseases tends to be higher, which is hypothetically associated with the increasing trend of cesarean sections in our society. Methods: This study design is analytical with a case-control approach using the odds ratio method. The study population consisted of 90 sick infants and babies, and 44 samples were obtained through a purposive sampling process with the following inclusion criteria: infants aged 0-12 months, respiratory disease (asphyxia, pneumonia, bronchopneumonia, bronchitis), autoimmune disease, rheumatoid arthritis, systemic lupus erythematosus (SLE), type-1 diabetes, multiple sclerosis (MS), Graves' disease. Results: Most infants were born with the Sectio Caesarea method of delivery; almost all infants have respiratory disease; a small number of infants suffer from autoimmune disease; most mothers who give birth with the Sectio Caesarea method are at risk of giving birth to infants with respiratory diseases. Infants born via Sectio Caesarea (SC) have a 0.590 or 0.6 times greater risk of respiratory disease than infants born via vaginal delivery; a small proportion of mothers who give birth via Sectio Caesarea (SC) are at risk of giving birth to babies with autoimmune diseases.Infants born via Sectio Caesarea (SC) have a 1.696 or 1.7 times greater risk of developing auto-immune disease than infants born via vaginal delivery. Conclusion: There is a relation between Sectio Caesarea (SC) and the incidence of respiratory and autoimmune diseases in infants at Kanjuruhan Hospital, Kepanjen Malang.